$^{6,7}$Li + $^{28}$Si total reaction cross sections at near barrier energies - A. Pakou; Musumarra, A.; Pierroutsakou, D.; N. Alamanos; Assimakopoulos, P.A.; Divis, N.; Doukelis, G.; A. Gillibert; S. Harissopulos; Kalyva, G.; Kokkoris, M.; A. Lagoyannis; et al. (Nucl. Phys. A, 2007)
Total reaction cross section measurements for the 6,7Li + 28Si systems have been performed at near-barrier energies. The results indicate that, with respect to the potential anomaly at barrier, 6Li and 7Li on light targets exhibit similar energy dependence on the imaginary potential. Comparisons are made with 6,7Li cross sections on light and heavy targets, extracted via previous elastic scattering measurements and also with CDCC calculations. Energy dependent parametrisations are also obtained for total reaction cross sections of 6,7Li on Si, as well as on any target, at near barrier energies. © 2006 Elsevier B.V. All rights reserved.
Keywords: (7Li; Comparison with previous results and model predictions; deduced; X); {28Si(6Li